Nature of Television Childbearing Shows and Mode of Delivery Preferences among Primiparous Women in Nairobi, Kenya - Musyoki, Christopher; Mberia, Hellen; Sikolia, Geoffrey (International Journal of Communication and Public Relation, 2024)
Purpose: To examine the effects of different types of TV childbearing shows on mode of delivery preferences among primiparous women in Nairobi, Kenya. Methodology: The study utilized a sequential mixed-methods approach, which involved 300 purposefully selected primiparous women from eleven sub-counties in Nairobi during routine child immunization schedules. Among the participants, 150 had vaginal deliveries, while the remaining underwent elective caesarean deliveries. Data collection was carried out through interviewer-administered questionnaires, focus group discussions, and in-depth interviews. Quantitative analysis involved the use of mean-weight scores, Chi-square tests, and Cramer's V using SPSS. Thematic analysis was conducted for qualitative data to comprehensively understand the research topic. The findings were presented through both numerical analysis and narrative exploration. Findings: Respondents who had elective caesarean deliveries scored higher in locating childbirth lessons and interest in viewing childbirth scenes. Vaginal delivery scored higher for observing long-term childbirth messages, with similar scores for reasons of watching TV childbirth shows. Talk shows were the most effective for childbirth learning (Ï†c = 0.52), with a small effect size for interest in viewing. Additionally, choosing mode of delivery as a repeated long-term message and having an idea of maternity as a reason for viewing had moderate size effects. The null hypothesis was rejected due to a significant correlation, with the ANOVA model explaining 87.9% of the variability. Locating lessons increased odds by 21.9%, repeated messages by 1.2%, and reasons for viewing by 3.3%, while interest in viewing childbirth scenes was not significant in the logistic regression. Qualitative analysis confirmed the rising prevalence of childbirth shows on mainstream TV. Unique Contribution to Theory, Practice and Policy: The study highlights how TV childbirth shows shape expectations and guide decisions regarding mode of delivery, contributing to media effect theories. In practice, healthcare workers need to actively engage with the content to address fears, concerns, and misconceptions influenced by these shows. Collaboration with content producers is crucial for authentic portrayals. Additionally, the study emphasizes the importance of media literacy programs and evidence-based guidelines to enhance informed decision-making.